Measurement of the cross-section of high transverse momentum vector bosons reconstructed as single jets and studies of jet substructure in pp collisions at root s=7TeV with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2014)
© CERN 2014 for the benefit of The ATLAS Collaboration, published under the terms of the Creative Commons Attribution 3.0 licence by IOP Publishing Ltd and Deutsche Physikalische Gesellschaft. This paper presents a measurement of the cross-section for high transverse momentum W and Z bosons produced in pp collisions and decaying to all-hadronic final states. The data used in the analysis were recorded by the ATLAS detector at the CERN Large Hadron Collider at a centre-of-mass energy of and correspond to an integrated luminosity of . The measurement is performed by reconstructing the boosted W or Z bosons in single jets. The reconstructed jet mass is used to identify the W and Z bosons, and a jet substructure method based on energy cluster information in the jet centre-of-mass frame is used to suppress the large multi-jet background. The cross-section for events with a hadronically decaying W or Z boson, with transverse momentum and pseudorapidity , is measured to be pb and is compared to next-to-leading-order calculations. The selected events are further used to study jet grooming techniques.